CSC413 - Introduction to Interactive Multimedia / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course will introduce the essential topics in multimedia application development. It includes concepts in hypermedia, basic process and techniques in multimedia application development such as effective combination of audio, video, animation and graphics. Beside that, the implications of data storage and retrieval methods and also the role of teamwork in multimedia application development will also be highlighted. It will also discuss on multimedia computer hardware, current multimedia software packages, multimedia application concepts, data manipulation, file formats, media storage and memory management and configurations. Applications of multimedia for mobile and the Internet will also be emphasized.